The Character Formation of Children in Japan: A Study of Japanese Children Textbook on Moral Education (Doutoku) - Unsriana, Linda; Ningrum, Rosita (Lingua Cultura, 2018)
The purpose of this research was to explore any underlying messages or moral principle in Japanese elementary schoolÂ textbook titled â€œWatashitachi no Doutokuâ€ and its correlation with the character formation of children in Japan. The methodÂ used in this research was the literature review that was derived from corpus data in the form of an original JapaneseÂ  manuscript. The corpus data were derived from textbooks that were still being used in Japan to date, in the form of originalÂ books in the Japanese language from the first grade to sixth grade elementary school, whereas the research method usedÂ a descriptive analysis method. The problem analysis was divided into four sections, including intrapersonal morality,Â interpersonal moral value, morality toward nature, and morality toward society. The conclusion indicates that characterÂ installment through special school subjects, namely moral education (doutoku), using Watashitachi no Doutoku influencesÂ character formation of elementary school children in Japan.